Mature teratoma in a neonate presenting as an intraoral cystic lesion: A case report - Singh, Srijan (Indian Journal of Child Health, 2020)
Teratomas are germ cell neoplasms that can occur in the cervical and craniofacial regions. A male neonate, antenatally diagnosed with intraoral cystic lesion, presented with a large 5 cm × 5 cm cystic swelling at birth arising from the palate. Alpha-fetoprotein levels of the patient were >1000 IU/L and beta-human chorionic gonadotropin levels were <0.9 mIU/ml. Computed tomography neck showed a cystic hypodense lesion of palatal origin measuring 4.9 cm × 4.3 cm × 4.6 cm. The baby developed respiratory distress at around 10 min of life and underwent coablation-assisted cyst excision of the lesion. Histopathology revealed mature cystic teratoma. Postoperatively, the baby was mechanically ventilated for 2 days and subsequently weaned off respiratory support.